Triple growth factor delivery promotes functional bone regeneration following composite musculoskeletal trauma. (June 2021) - Subbiah, Ramesh; Ruehle, Marissa A.; Klosterhoff, Brett S.; Lin, Angela S.P.; Hettiaratchi, Marian H.; Willett, Nick J.; Bertassoni, Luiz E.; García, Andrés J.; Guldberg, Robert E.
Abstract: Successful bone healing in severe trauma depends on early revascularization to restore oxygen, nutrient, growth factor, and progenitor cell supply to the injury. Therapeutic angiogenesis strategies have therefore been investigated to promote revascularization following severe bone injuries; however, results have been inconsistent. This is the first study investigating the effects of dual angiogenic growth factors (VEGF and PDGF) with low-dose bone morphogenetic protein-2 (BMP-2; 2.5 µg) on bone healing in a clinically challenging composite bone-muscle injury model. Our hydrogel-based delivery systems demonstrated a more than 90% protein entrapment efficiency and a controlled simultaneous release of three growth factors over 28 days. Co-stimulation of microvascular fragment constructs with VEGF and PDGF promoted vascular network formation in vitro compared to VEGF or PDGF alone. In an in vivo model of segmental bone and volumetric muscle loss injury, combined VEGF (5 µg) and PDGF (7.5 µg or 15 µg) delivery with a low dose of BMP-2 significantly enhanced regeneration of vascularized bone compared to BMP-2 treatment alone. Notably, the regenerated bone mechanics reached 60% of intact bone, a value that was previously only achieved by delivery of high-dose BMP-2 (10 µg) in this injury model. Overall, sustained delivery of VEGF, PDFG, and BMP-2 is a promising strategy to promote functional vascularized bone tissue regeneration following severe composite musculoskeletal injury. Although this study is conducted in a clinically relevant composite injury model in rats using a simultaneous release strategy, future studies are necessary to test the regenerative potential of spatiotemporally controlled delivery of triple growth factors on bone healing using large animal models. Statement of significance: Volumetric muscle loss combined with delayed union or non-union bone defect causes deleterious effects on bone regeneration even with the supplementation of bone morphogenetic protein-2 (BMP-2). In this study, the controlled delivery of dual angiogenic growth factors (vascular endothelial growth factor [VEGF] + Platelet-derived growth factor [PDGF]) increases vascular growth in vitro . Co-delivering VEGF+PDGF significantly increase the bone formation efficacy of low-dose BMP-2 and improves the mechanics of regenerated bone in a challenging composite bone-muscle injury model. Graphical abstract: Image, graphical abstract